Leadership and Implementation of Total Quality Management (TQM) on Employee Performance with the Mediating Role of Motivation - Yana Fajriah; Syamsul Alam; Edy Jumady; Heslina Heslina; Reski Arianty Akob (Advances in Human Resource Management Research, 2026)
Purpose: This study aims to examine the effects of leadership and Total Quality Management (TQM) on employee performance, with motivation as a mediating variable, at the Regional Drinking Water Company (Perumda Air Minum) in Makassar City. Research Method: This research employed a quantitative causal-explanatory approach. The population consisted of 163 permanent employees, and a census sampling technique was applied, in which all employees were selected as respondents. Data were collected via questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Results and Discussion: The findings indicate that leadership has a positive and significant effect on employee performance and employee motivation. TQM also positively and significantly affects employee performance and motivation. Furthermore, motivation has a significant positive effect on employee performance. Motivation was shown to mediate the relationships between leadership and performance, as well as between TQM and performance. These results suggest that effective leadership practices and the consistent implementation of TQM can improve employee motivation, ultimately enhancing organizational performance. Implications: The organization should strengthen leadership, improve employee engagement, maintain continuous quality improvement, and develop motivational strategies such as rewards, recognition, and career development programs. These actions are expected to enhance employee productivity and service quality.